Research on Pre-stored Data Processing Technology for Locomotive ATO System - Kai LI; Tiebing LI; Jiabo XIAO; Yong LIU; Fan JIANG; Qiao NING; Jiahuan ZHANG (机车电传动)
The locomotive ATO (automatic train operation) system is designed to replace the operation of drivers, which could achieve train running punctuality and energy saving on the premise of ensuring the safe and stable operation of the train. For supporting the precise optimization control strategy of the locomotive automatic train operation system, a large number of outstanding driver's experience operation data was collected to provide scientific guidance for automatic train control, and at the same time, the data of the special sections of the actual operating lines was collected to provide the basic navigation information for the control system. In order to provide the data to the locomotive ATO device in real time, a pre-stored data processing technology based on the train operation monitoring and recording device LKJ2000 was studied and implemented. The accuracy rate of pre-stored data output was 100%, which had been verified in the locomotive ATO system application of multiple railway companies. This technology can provide reliable pre-stored data for the locomotive ATO system, meeting the needs of actual applications.